Synthesis and studies of polymeric glyoxalimine oxamide and glyoxalimine malonamide complexes with some bivalent transition metal ions - Narang K.K.; Singh M.K.; Singh V.P.; Tare V.B.; Goglani A.K. (My University, 2025)
Complexes of the title ligands having the general composition MCl2l•xh2o where M =Cu(II), Ni(II), Co(II), Zn(II), Cd(II), Hg(II), L = glyoxalimine oxamide (GODH), glyoxalimine malonamide (GMDH) and x = 0, 1, 2, were synthesised. These were prepared either by solid-solution reaction of the metal chloride and the preformed polymeric ligands derived from glyoxal and oxaldihydrazide/malondihydrazide or by template synthesis using metal chloride, glyoxal, oxaldihydrazide/malondihydrazide in 1:1:1 molar ratio. The complexes are intensely coloured and highly insoluble in water as well as polar and non-polar organic solvents. They decomposed above 350°C without melting and were characterized by elemental analyses, magnetic, electronic and infrared spectral data, thermal (TG, DTG and DTA) and solid state conductance studies. © 1990, Taylor & Francis Group, LLC. All rights reserved.